Optimizing the Role of Community Advisors in Assisting Juvenile Clients with Diversion at the Mandau Sector Police - Rinaldi, Kasmanto; Yut Sepin, Fitria; Musa, M. (Faculty of Law, Universitas Pekalongan, 2024)
This study discusses the role of community advisors in the implementation of diversion for juvenile clients at the Mandau Sector Police. The research focuses on the implementation of guidance in accordance with Law No. 11 of 2012, which emphasizes the active role of community officers in the diversion process. The research methodology used is a normative empirical approach, combining normative legal studies with empirical data from the field. The findings indicate that the guidance provided by community advisors at the Mandau Sector Police complies with the provisions of Law No. 11 of 2012. Community officers play an active role in guiding, supervising, and overseeing the juveniles throughout the diversion process and in implementing the agreements reached. Additionally, community advisors are responsible for reporting to the court if the diversion agreement is not executed. However, the study also identifies several challenges in the guidance provided by community advisors, including a lack of consensus or agreement between the parties, a shortage of human resources or social workers, and the absence of community figures in the diversion process due to time constraints and the remote location of homes. Therefore, efforts are needed to improve the quality of human resources, involve community figures, and provide adequate facilities to support more effective diversion implementation.